Relatório de Estágio Profissional "Ser Professora: do sonho à realidade" - Susana Gonçalves Berenguer (2017)
This document incorporates a set of experiences throughout the Professional Training, inserted in the 2nd cycle of studies leading to the Master's degree in Physical Education Teaching in Basic and Secondary Education, Faculty of Sport of the University of Porto. The Professional Internship was held at the Gonçalves Zarco Elementary and Secondary School, located in the Autonomous Region of Madeira, under the guidance of a Faculty of Sport of the University of Porto teacher and a cooperating teacher from Gonçalves Zarco Elementary and Secondary School. In this document it is possible to know a little about what my trajectory was as a trainee teacher from overcoming my weaknesses, my evolution, to the most memorable moments. The report is written in the first person, in terms of structure is segmented into 5 chap ters: 1) Personal framing, a presentation is made on my reasons for chosing the life course as a profession; 2) Functional framework, it is regarding the professional placement, and the influences gained during the process; 3) Professional internship: understanding to expectations, a theoretical framework is made on the Professional Internship undertaken; 4) Internship: from theory to practice, focuses on the difficulties experienced and ways of overcoming these; 5) The rhythmic and expressive activities: the taboo of Physical Education - a study carried out in the Gonçalves Zarco Elementary and Secondary School of the Autonomous Region of Madeira, which portrays the research study undertaken.